Simulação numérica da temperatura do ar em um edifício com materiais construtivos alternativos - BORGES, Larissa dos Santos (2022)
The present study contemplates the thermal analysis of a residential building (10x10x3) simulated from alternative materials. Giving evidence to internal and external variables, which interfere thermally in any type of material. The substantial investigation of this research is to observe with greater attention the internal temperature of the air in the building, that is, the prediction of thermal sensation for the possible visitors. The references for the simulation were the year 2021 and the climate data for the city of Belém-PA. The tile, brick, floor, mortar and door elements were incorporated using alternative materials, while the others kept the traditional construction apparatus. By using the Heat Balance Method (HBM), nergyPlus, the main simulation software, operates and manipulates the data referring to the thermoenergetic performance, in order to predict the levels of thermal comfort in the simulated building. This study was not elaborated for merely comparative purposes between the elements, the purpose is to expend the reflection of the use of nonconventional materials in the thermal performance of a structure.